14.2=4.3(g+2)-3

Simple and best practice solution for 14.2=4.3(g+2)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14.2=4.3(g+2)-3 equation:



14.2=4.3(g+2)-3
We move all terms to the left:
14.2-(4.3(g+2)-3)=0
We calculate terms in parentheses: -(4.3(g+2)-3), so:
4.3(g+2)-3
We multiply parentheses
4.3g+8.6-3
We add all the numbers together, and all the variables
4.3g+5.6
Back to the equation:
-(4.3g+5.6)
We get rid of parentheses
-4.3g-5.6+14.2=0
We add all the numbers together, and all the variables
-4.3g+8.6=0
We move all terms containing g to the left, all other terms to the right
-4.3g=-8.6
g=-8.6/-4.3
g=+2

See similar equations:

| 13/2h=-2/3 | | 3^x=3^4 | | 0.7(k+5)=6.3 | | 3h=-2/3 | | 5x+7=5•(x+2) | | 18=13b | | 6g+g+3=17 | | 1/3(3-z)=1-1/3z | | (9x+3)-(13x-25)=77 | | (3x+17)+(15x-6)=15x+20 | | 4x-3,8=1,6+7x | | -148=6(3v-4) | | 37=3x+7+7x | | 1/2w=28 | | 6(-2a+5)=-2a-20 | | 37=3x | | -14p+20p=6 | | (4m-7)=(m-6m+4) | | x-33/4=18 | | -3(p-6)=12 | | 2(d+1)+3=9 | | -5n+15=30 | | -5d-14d+12d-6=8 | | -3(6x+1)=-93 | | 1/5k=35 | | -6w-5+2w=-13 | | y/4+y/6=3/5 | | 11x-15=16x+12 | | 8x-5=3x+37 | | -4n+n+6=-3 | | -x/5+11=13 | | 10x-17=43-2x |

Equations solver categories